Volatile and sensory characterization of white wines from three minoritary portuguese grapevine varieties - Piras, Simone (2020)
This work focused on the characterization of the volatile compounds and sensory profile of white wines produced from three minority grapevine varieties of Portugal namely ‘Malvasia’ (Colares), ‘Verdelho’ and ‘Galego Dourado’. The characterization took place using sensory and gas chromatography analysis. Furthermore, the data obtained were analysed through the use of multivariate analysis, which made it possible to evaluate the similarities and dissimilarities between the varieties. The results obtained show a differentiation of the wines produced from each grapevine variety but above all a differentiation of the two vintages was verified. The results obtained, both from a sensory and a chemical point of view, show an interesting oenological potential of these varieties, but still require further studies, in order to evaluate the influence of climatic effects on the profile of volatile compounds and also on the sensory profile